ATURAN POLIGAMI: ALASAN, TUJUAN DAN TINGKAT KETERCAPAIAN TUJUAN - Abdul Edo Munawar (IAIN Ambon, 2021)
This paper discusses the rules of polygamy: the reasons, objectives and the level of achievement of goals. The reason polygamy is regulated is because of the wrong practices of polygamy, such as siri polygamy and polygamy unilaterally without involving his wife. Regulated polygamy is to elevate women, avoid women from irresponsible practice of polygamy. Besides polygamy is also arranged to apply the principles of marriage, namely the principle of deliberation and democracy, the principle of creating a sense of security and peace in the family, the principle of Avoiding Violence, the principle of husband and wife relationship as a partner relationship and the principle of justice. The presence of regulations on polygamy has not yet fully created the principles of marriage. This research uses a juridical approach with a qualitative-library method. This study concludes that there are at least two reasons why the ideals of polygamy have not been realized. Ie, internally the rules of polygamy have not been binding, this is proven by the existence of a judge's ruling that authorizes polygamy siri without going through polygamy procedures. Externally the community still considers the registration of a marriage does not interfere with its marriage. The implication is that the existence of polygamy rules has not yet been fully achieved. Keyword: poligami rules, level of goal attainment